Determinants of Foreign Direct Investments in the Visegrad Group Countries - Wojciechowski, Liwiusz; Makieła, Kamil (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
The purpose of this paper is to investigate determinants of foreign direct investments (FDI) in the Visegrad Group countries. The theory indicates that FDI are mainly driven by market and efficiency seeking motives. Foreign investors are looking for a productive and relatively low‑cost business environment, which leads us to the assumption that productivity is one of key drivers of foreign capital. In order to verify this, we formulate a model based on a system of two equations: one for production to capture productivity and one for FDI to assess the influence of productivity on FDI. For robustness check, a number of macroeconomic and institutional factors are also considered. The study is conducted using a panel of 13 NACE industry sectors of the Visegrad Group countries in 2004-2013. The results indicate a positive, significant relationship between FDI and productivity as well as that market size, labour quality (and quantity), R&D expenditures and price changes over time are relevant FDI determinants at an industry level.